The Efficacy of Election Supervision by Gorontalo Regency's ESA (BAWASLU) in the 2020 Regional Head Elections - Nuna, Muten; Moonti, Roy; Kadir, Yusrianto (ANTMIND YOUTH EMPOWER FOUNDATION, 2024)
The study evaluates the performance of the Gorontalo Regency Election Supervisory Agency (BAWASLU) in overseeing campaign activities during the 2020 simultaneous Regional Head Elections (PILKADA). It scrutinizes the responsibilities placed on BAWASLU and its personnel, aiming for proficient enforcement of election laws to ensure equitable and transparent elections. Employing an empirical juridical approach, the research examines the community's legal frameworks and practical realities. Results indicate that BAWASLU's supervision of campaign activities, spanning traditional and social media platforms, fell short of expectations. Factors contributing to this shortfall include regulatory challenges and deficiencies in infrastructure and resources. Recommendations entail strengthening BAWASLU's oversight in alignment with existing regulations, emphasizing clarity in governmental directives, and ensuring sufficient resources. Moreover, community engagement and awareness initiatives are suggested to bolster electoral integrity and public trust..